Family Dynamics and Substance Abuse among Adolescents in Port Harcourt Metropolis (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This study examines the relationship between family dynamics and substance abuse among adolescents in Port Harcourt metropolis. The study specifically investigated the influence of parenting styles, family cohesion, and family conflict on adolescent engagement in substance use. The research adopted a correlational design, with a population of senior secondary school students in Port Harcourt. A sample of 400 adolescents was selected using a multistage sampling technique. Data were collected using a structured questionnaire adapted from standardized instruments and rated on a 4-point Likert scale. The reliability of the instrument was confirmed through a pilot study, yielding Cronbach’s alpha coefficients ranging from 0.79 to 0.85. Data were analyzed using Pearson Product-Moment Correlation Coefficient at a 0.05 level of significance. The results indicated a significant negative relationship between parenting styles and substance abuse (r = -0.412, p < 0.05), and between family cohesion and substance abuse (r = -0.388, p < 0.05). Conversely, a significant positive relationship was found between family conflict and substance abuse (r = 0.429, p < 0.05). These findings suggest that authoritative parenting and strong family cohesion serve as protective factors, while high family conflict increases the risk of adolescent substance use. The study concluded that family dynamics significantly influence substance abuse among adolescents in Port Harcourt metropolis. It was recommended that parents adopt authoritative parenting strategies, strengthen family cohesion, and manage conflict constructively. Additionally, school and community programs should incorporate family-focused interventions to reduce adolescent substance abuse. The study underscores the importance of considering family environments in developing policies and interventions aimed at mitigating substance abuse among adolescents.